Serological testing for celiac and autoimmune thyroid diseases in infertile women suffering from endometriosis, unexplained infertility and recurrent miscarriage - OZkan, S.; Kandemir, Y.; Kumbak, B.; Simsek, M.; Sapmaz, E. (Oxford Univ Press, 2014)
[Abstract Not Available]
30th Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUN 29-JUL 02, 2014 -- Munich, GERMANY